Internet of Things (IoT) and Arduino IDE as a Smart Water Quality Control for Monitoring in Catfish Ponds - Rizky Saparullah; Jesi Pebralia; Lucky Zaehir Maulana (International Journal of Hydrological and Environmental for Sustainability, 2024)
This research aims to develop a monitoring and control system for catfish pond water quality based on the Internet of Things (IoT). This system uses an ESP32 microcontroller Arduino Integrated Development Environment (IDE) connected to a SEN0131 pH sensor, DS18B20 temperature sensor, and HC-SR04 ultrasonic sensor to monitor water quality parameters such as pH, temperature, and water level. Data obtained from these sensors is stored in a real-time database that can be accessed remotely via the Blynk application. This system is also equipped with a water pump and solenoid valve that automatically controls water filling and discharge based on detected water quality parameters. The test results show that the system has an average accuracy of 99.45% and high precision with an average relative standard deviation of 0.01% in detecting water quality parameters. System operation was carried out for 27 days. The system can run continuously or non-stop. data is input in real-time to blynk, so it can be monitored and controlled from anywhere.